2007
DOI: 10.1523/jneurosci.0369-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Prelimbic/Infralimbic Inactivation Impairs Memory for Multiple Task Switches, But Not Flexible Selection of Familiar Tasks

Abstract: Behavioral flexibility, in the form of strategy switching or set shifting, helps animals cope with changing contingencies in familiar environments. The prelimbic (PL) and infralimbic (IL) regions of the rat prefrontal cortex (PFC) contribute to this ability so that rats trained to use one strategy have difficulty learning a new one if the PL/IL is inactivated. Thus, the PL/IL mediates learning new tasks in place of old ones, but it may also be required to switch between familiar tasks. To test this hypothesis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
134
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(148 citation statements)
references
References 56 publications
9
134
5
Order By: Relevance
“…This lower number of errors could reflect an enhanced cognitive flexibility of EC rats, since during the first days rats have to avoid re-entering in a previously visited arm against their natural tendency to do it. Interestingly, the PFC plays a key role in cognitive flexibility (Birrell and Brown 2000;Ragozzino 2002;Robbins and Roberts 2007), which could be the main role of the PFC in the performance of the radial-maze win-shift paradigm (Gisquet-Verrier and Delatour 2006;Rich and Shapiro 2007). Therefore, the faster learning of the task by EC rats could be due to changes in the PFC that would enhance their ability to adapt to the changes faced across the different steps of learning of the task.…”
Section: Spatial Working Memorymentioning
confidence: 99%
“…This lower number of errors could reflect an enhanced cognitive flexibility of EC rats, since during the first days rats have to avoid re-entering in a previously visited arm against their natural tendency to do it. Interestingly, the PFC plays a key role in cognitive flexibility (Birrell and Brown 2000;Ragozzino 2002;Robbins and Roberts 2007), which could be the main role of the PFC in the performance of the radial-maze win-shift paradigm (Gisquet-Verrier and Delatour 2006;Rich and Shapiro 2007). Therefore, the faster learning of the task by EC rats could be due to changes in the PFC that would enhance their ability to adapt to the changes faced across the different steps of learning of the task.…”
Section: Spatial Working Memorymentioning
confidence: 99%
“…In the current model, both strategy switching and reversal can be learned within the same network, since reversal in our model corresponds to simply changing the reward location. Other inconsistencies come from the study of Rich and Shapiro (2007), who have shown that mPFC is involved only during first strategy switches and it does not seem to play a role during subsequent switches. Our model cannot provide plausible explanation for these data.…”
Section: Neural Substrates For the Strategy-selection Networkmentioning
confidence: 99%
“…Our model cannot provide plausible explanation for these data. In summary, mPFC might be considered as a biologic locus for the selection network, but in this case (i) a separation of the gating network into at least two different parts is required to take into account the reversal data (Young and Shapiro 2009), and (ii) an extension to the model is required to explain how the strategy switching is performed after more than a few subsequent switches (Rich and Shapiro 2007).…”
Section: Neural Substrates For the Strategy-selection Networkmentioning
confidence: 99%
“…First, it is known that strategy switches and reversals in the plus maze are mediated by different subareas of the prefrontal cortex, medial PFC (mPFC) and orbito-frontal (OFC) cortex, respectively [6,7]. Moreover, there is experimental evidence suggesting hierarchical organization of these two subareas [14].…”
Section: Discussionmentioning
confidence: 99%
“…Large body of animal studies suggest a large variety of navigational strategies, which depend on sensory input of different modalities [1]. Existing lines of experimental research focus on (i) how the different strategies are implemented in the brain and what memory systems support them [2][3][4][5]; and (ii) what is the mechanism of selection between different strategies and corresponding memory systems during ongoing behavior [6][7][8]. In particular, a series of animal studies in the plus maze ( Figure 1A) provided an insight into the role of hippocampus (HPC), dorsolateral striatum (DLS) and prefrontal cortex (PFC) in learning the tasks in which changing reward contingency forced the animals to use either a place strategy or a response strategy.…”
Section: Introductionmentioning
confidence: 99%